2020
DOI: 10.5763/kjsm.2020.38.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Objective versus Self-reported Physical Activity and Cardiovascular Disease Risk Factors

Abstract: Purpose:The main purpose of this study was to compare the relationships between physical activity (measured using an accelerometer vs. self-reported) and cardiovascular disease risk factors. Differences in accelerometry physical activity between 10-minute bouts and total bouts were also compared. Methods: Data originated from the Korea National Health and Nutrition Examination Survey. Logistic regression was used to predict cardiovascular disease risk from physical activity levels. Results: Self-reported physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…In both studies, large differences were found between PA time measured through questionnaires and accelerometers [19]. Moreover, PA had stronger associations with cardiovascular disease and metabolic syndrome when it was measured using accelerometers than questionnaires [20,21].…”
Section: Introductionmentioning
confidence: 90%
“…In both studies, large differences were found between PA time measured through questionnaires and accelerometers [19]. Moreover, PA had stronger associations with cardiovascular disease and metabolic syndrome when it was measured using accelerometers than questionnaires [20,21].…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, improving urban open space has long-term implications for the community, such as enhancing social capital, the interaction between people, connectivity, and walkability. Planning literature recommends that having access to a neighborhood park and natural surroundings can affect mental and physical health, reduce chronic diseases and stress, and elevate individual performance [19,20].…”
Section: Open Space In Abu Dhabimentioning
confidence: 99%
“…특히, ActiGraph 가속도계 도구의 중•고 강도 신체활동(moderate to vigorous physical activity; MVPA) 강도의 경우, 급내 상관계수(ICC)는 0.99, 절대백분율오차(APE)는 3.7%, 변동계수(CV)는 4.9%로 보고되었다 (McClain et al, 2007). 가속도계로 측정된 객관적인 신체활동 자료는 자기 보고형 설문 지와 비교하여 성인들의 심혈관 대사질환 요인의 위험성을 정확 하게 예측할 수 있는 것으로 보고하고 있다 (Atienza et al, 2011;Sternfeld et al, 2019;Sung et al, 2020) (Hooker et al, 2022;Troiano et al, 2008) (Marotta et al, 2010). 대사중후군은 미국 심장협회(AHA)와 국립 심장, 폐, 혈액 연구소(NHLBI)에서 제시한 요인과 위험 기준을 적용하였으나 (Grundy et al, 2005), 허리둘레 의 경우 한국비만학회가 제시한 위험기준을 적용하였다 (Kim et al, 2021)…”
unclassified